Effects Of Feeding Metabolites From Lactobacillus Plantarum Strains On Lipid Metabolism, Gut Morphology And Growth Performance Of Broiler Chickens - Nguyen, Tien Thanh (2008)

(untitled)
Four experiments were conducted to study the effects of feeding metabolite combinations produced from six strains of L. plantarum on the performance of broiler chickens. The inhibitory activity of different combinations of metabolites produced by locally isolated L. plantarum against various pathogens was studied in the first experiment. Sixty-three combinations of metabolites obtained from 6 strains of L. plantarum: UL4, TL1, RS5, RI11, RG14 and RG11 were equally and homogenously mixed. The inhibitory activity was then determined against 5 selected indicators, which are E. coli, L. monocytogenes, S. typhimurium, Vancomycin resistant enterococci (VRE) and Pediococcus acidilactici. The inhibitory activity was measured based on the diameter of inhibitory zone. Four combinations with the highest inhibitory scores were identified. The combination of four strains RS5, RI11, RG14 and RG11 has given the highest score, followed by the combinations of TL1, RG14 and RG11 strains, combinations of TL1, RI11 and RG11 strains, and combinations of TL1, RS5, RI11 and RG14 strains. These results indicate that different combinations of metabolites had different antibacterial activity, which could be used in food and feed industries. Combinations of different metabolites further enhance the antimicrobial activity. Four combinations of metabolites with the highest inhibitory activity were used in the following experiment to study the performance of broiler chickens. A total of 432 day-old male Ross broiler chicks were raised to 42 days of age in deep litter system. Each pen consisted of 12 chicks and was randomly allocated to the open house with wood shavings litter. The birds were vaccinated (IB-ND live vaccine, Fort Dodge, USA) against infectious bronchitis (IB) and Newcastle disease (ND). The birds were also vaccinated with IBD vaccine (MyVac UPM93, Malaysia) against infectious bursal disease (IBD) on day 14. Wing band was applied to all of the birds for identification. Water and feed were provided ad libitum. The feed intake and body weight were recorded weekly. The starter and finisher diets were offered to the birds from 0 - 21 and 22 - 42 days of age, respectively. The dietary treatments consisted of: (i) corn-soybean based diet without antibiotic (-ve control) diet; (ii) basal diet with neomycin and oxytetracyclin (+ve control); (iii) basal diet supplemented with 0.3% metabolite combinations of L. plantarum RS5, RI11, RG14 and RG11 (Com3456); (iv) basal diet supplemented with 0.3% metabolite combinations of L. plantarum TL1, RG14 and RG11 (Com256); (v) basal diet supplemented with 0.3% metabolite combinations of L. plantarum TL1, RI11 and RG11 (Com246); (vi) basal diet supplemented with 0.3% metabolite combinations of L. plantarum TL1, RS5, RG14 and RG11 (Com2456). Greater final body weight (BW), weight gain (WG), average daily gain (ADG), volatile fatty acids (VFA) and lower feed conversion ratio (FCR) were significantly (p<0.05) found in the birds fed with the 4 metabolite combinations.Supplementation of metabolites combination also increased faecal lactic acid bacteria (LAB) population, villi height of small intestine and lowered plasma and meat cholesterol and faecal Enterobacteriaceae (ENT) population. In the third experiment, the effect of feeding different dosages of Com3456 obtained from the second experiment on the performance of broiler chickens was studied. A total of 504 day-old male Ross broiler chicks were grouped into 7 treatments and offered with different diets: (i) standard corn-soybean based diet (negative control); (ii) standard corn-soybean based diet + neomycin and oxytetracycline (positive control); (iii) standard corn-soybean based diet + 0.1% metabolite combination of L. plantarum RS5, RI11, RG14 and RG11 strains (Com3456); (iv) standard corn-soybean based diet + 0.2% of Com3456; (v) standard corn-soybean based diet + 0.3% of Com3456 (vi) standard corn-soybean based diet + 0.4% of Com3456 and (vii) standard corn-soybean based diet + 0.5% of Com3456. Supplementation of Com3456 with different dosages improved growth performance, reduced ENT and increased LAB count, lowered plasma and meat cholesterol, and increased villi height of small intestine and volatile fatty acids (VFA). Nevertheless, abdominal fat deposition was not affected by Com3456 metabolites. Only slight increase of antibody titers against Newcastle disease, infectious bronchitis and infectious bursal disease was found in those birds supplemented with the metabolites. Treatment with 0.2% Com3456 had the best results with minimal cost, especially in terms of growth performance, FCR and plasma and meat cholesterol reduction among other dosages. These results indicate that 0.2% is optimum dosages to be included in the diets of broiler chickens in order to replace antimicrobial growth promoters (AGP).In the last experiment, the very low-density lipoprotein (VLDL) lipid profiles, intestinal LAB count and bile salts deconjugation of LAB were studied. The results showed that metabolite combinations supplemented in broilers feed reduced free cholesterol and cholesterol esters in VLDL particles and increased LAB count in digesta of small intestine. The results also suggest that LAB are able to deconjugate bile salts and lead to the increase of cholesterol utilization for synthesizing new conjugated bile salts. These properties of metabolite combinations in the diets of broiler chickens contribute to the reduction of cholesterol in plasma and meat.